Responses of maize, sorghum and millet host plants infestation by Striga hemonthica - Kim, S.K.; Akintunde, A.; Walker, P. (Elsevier, 1994)
Twelve samples of Striga hermonthica seed were collected from four host crops [millet (4), sorghum (4), a sorghum/millet intercrop (3) and maize (1)] from all the main areas of S. hermonthica infestation in Nigeria and were tested on eight genotypes of three test crops [maize (4), sorghum (2) and millet (2)] in two screenhouse trials. Plants of each test genotype were sown in pots and heavily infested with S. hermonthica. Emergence count of the parasite, test crop damage rating (1–9), and test crop plant height were measured at 9 weeks after planting. The effects of genotypes, samples and their interaction for all three traits measured were highly significant (p = 0.001). Of the 12 samples of S. hermonthica, all have high emergence on both maize and sorghum. Seven samples gave low emergence on millet genotypes and two none at all. Three of the four samples from millet sources gave higher parasite emergence on sorghum and maize than on millet. For Striga damage rating, millet had the lowest average scores, followed by maize and sorghum. The responses of maize genotypes to samples from millet and sorghum sources were significantly different. Millet genotypes also had different responses to the samples from millet sources. For plant height differences, samples from sorghum sources interacted significantly with test maize genotypes, and millet samples with sorghum genotypes. The results indicate that both intercrop and intracrop strains of S. hermonthica are present in Nigeria.